Beginner Teachers’ Encounters with the Reality of Education: Case of the “Teach First Lithuania!” Program - Lebedytė-Mečionienė, Indrė (Acta Paedagogica Vilnensia, 2022)
Beginning teachers are confronted with certain established norms, power relations, cultures and systems in schools and in education in general at the beginning of their careers. They are in a constant field of tension and can be much more sensitive to observing and questioning standards than those who have been operating in that system for a long time. In order to maintain a critical and change-oriented approach, it was chosen to describe the ideas of critical pedagogy and to analyze teachers’ experiences through this prism. Nine beginners in teaching from “Teach First Lithuania” were interviewed about their encounters with the reality of education and the choices that followed. The findings of the study revealed the prevailing hierarchical relationships in the school (often based on fear or tension); the prevalence of various types of falsification – when documents do not correspond to reality; orientation to the curriculum, standardized tests, and exams; the formation of academic classes and the “norm” of labeling – phenomena that form the habitus of the weaker and contribute to social reproduction in education. For all participants in the study, the relationship with the students is the most important, but teachers who are still teaching admit that results became very significant (due to pressure from parents, administration, and society). Staying in public schools is most motivated by a sense of appreciation, good relationships with colleagues, and commitment to students. Decisions to abandon teaching are most motivated by a heavy workload and lack of freedom.
Keywords: beginner teachers; “Teach first Lithuania”; critical pedagogy; reality shock; social reproduction in education; educational reforms